Odpowiedzi

Najlepsza Odpowiedź!
2010-01-05T15:52:06+01:00
A) 5/4 √48 - 3/4 √12= 5/4√12*4 - 3/4√12= 2*5/4√12- 3/4√12=
10/4√12- 3/4√12= 7/4√12

b) 2/5 √40 + 1/6√90=2/5√10*4 + 1/6√10* 9=
2*2/5√10 + 3*1/6√10= 4/5√10+3/6√10=
24/30√10 + 15/30√10= 39/30√10= 13/10√10

c) √20/3 + √45/4 - √80/2=
√4*5/3 + √9*5/4 - √16*5/2= 2√5/3 + 3√5/4 - 4√5/2=
8√5/12+ 9√5/12 - 24√5/12= -7√5/12

d) 2√8/3 - 3√18/5 - √56/2= 2√2*4/3 - 3√9*2/5 - √56/2=
4√2/3 - 6√2/5 -√56/2= 20√2/15 - 18√2/15 - √56/2
2√2/15 - √56/2

e) 1/5 √7 - 1/2 √28=1/5√7 - 1/2√7*4= 1/5√7 - 2*1/2√7=
1/5√7 - √7 = - 4/5√7